Marketing : real people, real choices - Solomon, Michael R.; Marshall, Greg W.; Stuart, Elnora W. (Upper Saddle River, NJ : Pearson Education International, 2009)
Introducing marketing from a real-world, practical perspective, this text lets students see how people just like them are actually doing real marketing. Case studies focus on companies where the answers are not clear-cut.
'Pearson international edition'--Cover.
Includes folded'tear-out template' which comprises study plan and world map.
Includes bibliographical references and index.
Keywords: Marketing -- Vocational guidance